(untitled) (Biological Sciences - PJSIR, 2002)
Quarantine phytopathogenic analysis of different sorts of tomato and cucumber seeds used in greenhouses in Russian Federation was studied. The common number of fungi and bacteria colonizing the outside and inside of seeds were determined. The characterization of micromycetes and bacteria complex disseminating the seeds was established. The phytotoxic infectious microorganisms were isolated. The negligible effect of some physical and chemical factors in seeds disinfectant was shown. The high antagonistic activity against phytopathogens as a new method of biocontrol with Trichoderma harziamum was proposed.